Una Aproximación al Arte Digital. - Valencia Ramos, Arturo (UNIVERSIDAD DE SONORA, 2023)
Abstract. This article presents in general a vision, an approach, to digital art. It is aimed at an audience that barely shows its interest in the subject that undoubtedly is becoming more and more relevant, especially if we consider the most recent debates around artificial intelligence and its impact globally. The arrival and massive use of the internet has contributed both to the production, dissemination, and storage of digital art, while it has become its natural habitat: most digital production is disseminated on social networks and in established sites for that purpose. The article states that digital art has been linked to technological advances and emerges in a period of our history in which technology has become a fundamental element of culture and society.